Lembranças da escola: um estudo sobre os sentidos da experiência escolar para os alunos - Silva, Ana Cristina Pimentel dos Santos (2009)
This research aims to verify which aspects interfere in the relationship that students establish with the school and the apprenticeship. This dissertation focuses the memories from the experiences students had at school. The hypothesis is that some feelings about studying came from schooling experience. Then, is important to know the perceptions and senses that students construct in their schooling. Other references and meanings are important and have to be considered, but this work is about the school. In order to carry on this research we interviewed four undergraduate students, two of them with public and two with private school background, according to the Brazilian standards. We made a qualitative analysis of the elicited data, according to the proposal of Aguiar and Ozella (2006). This analysis clearly demonstrated the important role played by the quality of the activities offered by school and its connection with the feelings displayed by the students towards the institution. School education involves relationship among individuals, so we must take into consideration senses, meanings, feelings, emotions, histories and personal characteristics that interfere in the learning process. These results allowed us to confirm how important it is to consider the subjective dimension of schooling experience. The theoretical and methodological approach of the Socio-historical Psychology helps us to recognize this